Development of a Self-Healing Strategy With Multiagent Systems for Distribution Networks - Leite, Jonatas Boas [UNESP]; Sanches Mantovani, Jose Roberto [UNESP] (Ieee-inst Electrical Electronics Engineers Inc, 2017)
The increase in information and communication technologies in the electric power system has led the distribution network to a new evolutionary stage known as a smart grid. In this scenario, automatic local switching plans based on an understanding of the network topology and load behavior allow the implementation of self-healing strategies. Self-healing aims at the minimization of the number of switching operations within the shortest time interval to restore the maximum load affected by a fault and to preserve distribution network operation limits. In this paper, multiagent system concepts are employed to develop a self-healing strategy, where all switching local agents have some awareness regarding the current network state and work cooperatively to reach the global purpose of distribution network automatic restoration.
Keywords: Distribution network; smart grid; self-healing; multiagent systems